Alternativas para la reducción de la contaminación del agua y el aire debido a la agricultura - Vera Olea, Milton Miguel (2022)
The main water pollutants from agriculture are nutrients (especially nitrogen and phosphorus from chemical and natural fertilizers), pesticides, saline sediments and organic matter. Livestock and agriculture, the main source of ammonia emissions, are in fact the elements that contribute to air pollution. Forty percent of these emissions are the result of livestock, fertilizers and biomass combustion. The deliberate burning of forest plants for deforestation is also responsible for these pollutants. The information obtained was carried out using the analysis, synthesis and summary technique, with the purpose of informing the reader about the alternatives for reducing water and air pollution due to agriculture. From the above detailed it was determined that the intensification of agriculture has improved in recent years, which has contributed to expand the use of water and has also led to an increase in the hundreds of water pollution, which affects ecosystems and human health. Water pollutants from unsustainable agricultural practices (chemical fertilizers, pesticides, saline sediments and organic matter), represent an extreme danger to human health and the planet's ecosystems. Air pollution from pesticides is promoted through plant applications, which cause air pollution, in addition to herbicide programs and other crop applications. Burning and forest fires that spread from them are the major source of black carbon, a risk to human and environmental health.